Parental Alienation in Quebec Custody Litigation - Zaccour, Suzanne (Les Cahiers de droit, 2018)
This article is a study of all Quebec custody cases dealing with parental alienation in 2016. It explores the definitions, findings and implications of parental alienation in legal disputes, in light of the models of parental alienation and parental alienation syndrome described in the academic literature. This research confirms feminists’ skepticism toward the use of parental alienation in custody litigation. It concludes that alienation has varying and inconsistent definitions in law, that there is a considerable disconnect between scientific knowledge and judges’ understanding of alienation, and that the concept of parental alienation in law is ambiguous and over-inclusive, seemingly to the detriment of mothers. There is a dire need for clearer and stricter guidelines on the use of parental alienation to ensure the accuracy, coherence, and fairness of the case law.